Sebuah ANALISIS PENGARUH PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR IPS TERPADU SISWA - Prasetyo, Bayu; Hestiningtyas, Widya; Winatha, I Komang (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Jurai Siwo Lampung, 2022)
Students' learning outcomes can not be achieved with a quick process and less effort. Everything takes a relatively consistent process and requires roles from various stakeholders in order to achieve the learning goals. The parents' roles are crucial because they become the first education place for children. The process of guidance along the learning activities since early childhood, attention, encouragement, and motivation becomes crucial issues for children. The research aims to determine the influence of parental attention on students' learning achievement of the Integrated Social Science at grade VII and VIII SMPN 1 Palas. The research used a verificatively decriptive method with an ex post facto and survey approcah. The population consisted of 294 students at grade VII and VIII of this school. The sampling technique was a probability sampling with a simple random sampling. The hypotheses was F test. The research results showed that there was influence of parental attention on students' learning achievement of the Integrated Social Science. It can be seen from the value of t count of 4,736 and t table of 1,654 which means that the t count is higher than the t table.